1.6‐2.6 GHz continuous Class‐F power amplifier with gain and power‐added efficiency flatness enhancement by negative feedback structure. Issue 7 (22nd February 2019) - Qi, Chongchong; Luo, Yonglun; Feng, Xuxu; Dong, Chaoran
Abstract: This article studies the feasibility of applying negative feedback structure in continuous Class‐F power amplifiers to improve the gain and efficiency flatness. The operation principle of the negative feedback structure under small and large signal input states is presented. The gain and efficiency are increased at high frequency part and decreased at low frequency by introducing the negative feedback structure, and the flatness is improved. Multiharmonic bilateral pull is used to obtain the optimum impedances, to reduce the interaction between source and load side, and the influence of parasitic parameters. A highly flatness amplifier with the negative feedback structure is designed operating at 1.6‐2.6 GHz by using a Cree GaN HEMT CGH40010H device. The measurement results show a gain flatness of 1.1 dB, and a power‐added efficiency flatness of 9%.